THE EFFECT OF PERSUASIVE COMMUNICATION AND INFLUENCER SOURCE CREDIBILITY ON THE PURCHASE DECISION OF TIMEPHORIA LIPCREAM PRODUCTS ON INSTAGRAM SOCIAL MEDIA @TASYAFARASYA WITH BRAND AWARENESS MEDIATION - Azahra Winarla; Yuliani Rachma Putri (Pena Cendekia Insani, 2026)
The purpose of this study is to analyze the influence of persuasive communication and credibility of influencer sources on purchasing decisions for Timephoria lip cream products on Instagram social media @tasyafarasya with brand awareness as a mediating variable. Instagram is used as a digital marketing medium that is able to disseminate messages in a personal and persuasive manner, thereby influencing consumer perceptions and behavior in the purchasing decision-making process. This study uses a quantitative approach with a survey method. The research sample consisted of 400 respondents who are active Instagram users, follow the @tasyafarasya account, and have purchased Timephoria lip cream products. Data collection was carried out through an online questionnaire, while data analysis used measurement model testing (outer model), structural model (inner model), and path analysis. The results showed that persuasive communication had a significant effect on purchasing decisions (t = 23.427; p < 0.05) and the credibility of influencer sources also had a significant effect on purchasing decisions (t = 28.076; p < 0.05). In addition, the credibility of the influencer source significantly influences purchasing decisions through brand awareness (t = 8.775; p < 0.05), and persuasive communication significantly influences purchasing decisions through brand awareness (t = 14.241; p < 0.05 and t = 5.026; p < 0.05). Simultaneously, persuasive communication and the credibility of the influencer source significantly influence purchasing decisions through brand awareness (t = 5.130; p < 0.05 and t = 4.892; p < 0.05). The overall results of the path analysis show a significant and positive influence (p = 0.000). These findings confirm that persuasive communication and influencer credibility through brand awareness have a positive influence on the purchasing decisions of Instagram followers @tasyafarasya.